Can An Anti-Dumping Policy Be Substituted For Predatory Pricing? - Zaid, Zaid; Gustiyani, Rininta; Kirana, Andita Hilmi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
One of the most contentious issues in international commerce is anti-dumping (AD). And among the controversies of this AD rule, there is also what is considered in “conflict” with business competition law, both in terms of the purpose of the regulations and from the rules themselves. One of them is related to predatory pricing. Therefore, this study aims to conduct further analysis regarding the possibility of predatory pricing rules in substituting anti-dumping regulations in Indonesia. Based on these aims, this study employs a normative method with a statutory and conceptual approach. This study then reveals that dumping can be classified as a predatory pricing practice in terms of indications and impacts. However, the legal consequences and consequences of the two are different. So it would be impossible if anti-dumping arrangements were substituted with predatory pricing. Nevertheless, this research still supports that anti-dumping regulations are included in the regulation or law prohibiting unfair business competition and monopolistic practices because the practice of dumping itself is an unfair business competition practice.